Adherence to Long-Term Follow-up in Patients With Sporadic Vestibular Schwannomas Managed With Serial Observation. Issue 3 (August 2021) - Raymond, Mallory; Ghanouni, Arian; Brooks, Kaitlyn; Clark, Sarah M.; Mattox, Douglas E.
Objectives: To examine the long-term adherence to serial imaging of patients with sporadic vestibular schwannoma and analyze factors associated with being lost to follow-up. Study Design: Retrospective chart review with telephone interview. Setting: Single tertiary care center. Methods: Patients with a sporadic vestibular schwannoma and started on observational surveillance management between January 2005 and December 2010 were included. Demographic data, tumor size, hearing and vestibular changes, and follow-up length were recorded. Patient factors were analyzed for association with being lost to follow-up. Results: In total, 122 patients were included with a median length of follow-up of 5 months (range, 0-146). After initial surveillance, 22.1% (n = 27) of patients had a change in management to either microsurgery or radiosurgery. Of the remaining 77.9% (n = 95), nearly half (44.2%, n = 42) never returned for a second visit, and all but 3 were eventually lost to follow-up. There was no association between sex, race, age at diagnosis, initial tumor size, insurance status, household income, or driving distance to hospital and being lost to follow-up. Of 26 interviewed patients initially lost to follow-up, 11 (42.3%) sought care at another institution, 5 (19.2%) chose to no longer receive care, 1 (3.8%) had transportation difficulties, and 9 (36.4%) had poor understanding of their diagnosis or instructions. Conclusions: The length of follow-up for patients undergoing surveillance of sporadic vestibular schwannoma varies widely, and patients are commonly lost to follow-up. Further efforts should be made to identify at-risk patients and provide adequate education to improve long-term surveillance.